A study of dermoscopic features of nail psoriasis - Yorulmaz, Ahu; Artuz, Ferda (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Dermoscopy is a non-invasive imaging method that enables the evaluation of pigmented and non-pigmented skin lesions. More recently, dermoscopy has been recognized as an effective tool in the diagnosis of nail diseases. Aim: To evaluate the dermoscopic features of nail psoriasis and to assess the relationship between these features and disease severity. Material and methods : A total of 67 patients with clinically evident nail psoriasis (14 women, 53 men) were prospectively enrolled. Following a thorough clinical examination, patients were graded according to the Nail Psoriasis Severity Index and physician’s global assessment score. A dermoscopic examination of all fingernails and toenails was performed using a videodermatoscope. Mann-Whitney U and 2 tests were used for statistical analysis, with a significance threshold of p < 0.05. Results: The most frequently observed dermoscopic features were splinter haemorrhage (73.1%), pitting (58.2%), distal onycholysis (55.2%), dilated hyponychial capillaries (35.8%) and the pseudo-fiber sign (34.3%). The pseudo-fiber sign, dilated hyponychial capillaries, nail plate thickening and crumbling, subungual hyperkeratosis, transverse grooves, trachyonychia, pitting and salmon patches were positively associated with disease severity. Conclusions : The pseudo-fiber sign described in this study appears to be a novel dermoscopic feature of nail psoriasis. We have demonstrated positive associations between a number of dermoscopic manifestations and disease severity. Further studies are required to support the present findings.